2011
DOI: 10.1002/pola.24564
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photovoltaic behaviors of narrow‐band‐gap π‐conjugated polymers composed of dialkoxybenzodithiophene‐ and thiophene‐based fused aromatic rings

Abstract: Abstractπ‐Conjugated polymers, PBDT‐CNETT and PBDT‐CNECPDT, were prepared by the Stille cross‐coupling polymerization. Optical and thermal properties of the obtained polymers were investigated by UV–vis spectroscopy and thermogravimetric analysis. PBDT‐CNETT and PBDT‐CNECPDT exhibited very narrow band gaps of 1.39 and 1.13 eV, respectively. Highest occupied molecular orbital energy levels estimated by surface analyzer were −5.17 and −5.11 eV for PBDT‐CNETT and PBDT‐CNECPDT, respectively. The solar cells based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The estimated optical band gaps of P1 and P2 are in a good agreement with the literature data for a CPDT-fluorene copolymer bearing dicyanovinyl groups at the bridge positions (E g ¼ 1.13 eV). 19 Polymer P3 also demonstrates three distinct bands in the absorption spectrum. The broad low-energy band has an offset at approximately 700 nm corresponding to the E g * 1.76 eV.…”
Section: Synthesis and Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…The estimated optical band gaps of P1 and P2 are in a good agreement with the literature data for a CPDT-fluorene copolymer bearing dicyanovinyl groups at the bridge positions (E g ¼ 1.13 eV). 19 Polymer P3 also demonstrates three distinct bands in the absorption spectrum. The broad low-energy band has an offset at approximately 700 nm corresponding to the E g * 1.76 eV.…”
Section: Synthesis and Characterizationmentioning
confidence: 98%
“…It should be noted that application of a similar cyanovinyl monomer for designing benzodithiophenebased conjugated polymers was reported previously by other research group. 19…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that their optical band gaps were 1.92 and 2.27 eV, respectively. For the construction of small band gap polymers, many examples [40,41] have demonstrated that utilizing alternative electron deficient and electron rich units is an effective method. The difference of optical band gap is particularly owed to the different molecular structures and the number of electron donating functional groups.…”
Section: Uv-vis Absorption and Fluorescence Emission Spectramentioning
confidence: 99%
“…The derivatives, P7, P8 and P9 were designed and a 1.13 eV band gap was reported in the polymer P8 (Scheme 4). 23,24 Besides introducing electron-rich or electron-deficient side groups, designing conjugated polymer with quinoid structures is another effective way to reduce band gap, and this strategy has been already proved to be very effective in other conjugated systems. For BDT-based polymers, P10 was designed based on this strategy.…”
Section: Bdt-based Polymers With Thiophene or Its Derivativesmentioning
confidence: 99%